Association between mental health and mindfulness in eating among undergraduate medical students in Universiti Sains Malaysia, Health Campus, Kubang Kerian, Kelantan - Qing, Ang Shu (2021)
Medical education is well known for its challenging and stressful nature that may cause medical students to have a higher risk of mental health problems. On the other hand, mindful eating concerns awareness of dietary habits, while its absence is usually associated with anxiety, negative affect as well as binge eating. The purpose of this study is to evaluate mental health and mindfulness in eating as well as their association among undergraduate medical students in USM, Health Campus. The respondents were recruited through convenience sampling and 158 responses were included in the analysis. Socio-demographic characteristics, mental health and mindfulness in eating of respondents were obtained. Questionnaires namely Depression, Anxiety and Stress Scale (DASS-21) as well as Mindful Eating Questionnaire (MEQ) were used in the data collection form. Among 158 respondents, 69.0% were female whereas 31.0% were male. According to DASS-21, the prevalence of depression, anxiety and stress among respondents were 38.6%, 51.3% and 32.2% respectively whereas the mean MEQ summary score was 2.82±0.26 according to MEQ, which is considerable. Significant, fair inverse association were found between depression score and mindfulness in eating (r=-0.33, p<0.001), anxiety score and mindfulness in eating (r=-0.34, p<0.001) as well as stress score and mindfulness in eating (r=-0.37, p<0.001), with higher depression score, anxiety score and stress score associated with lower mindfulness in eating. In conclusion, it is important to pay attention on mental health and mindfulness in eating among undergraduate medical students as they are associated and neglection might lead to problems such as disordered eating behaviour such as binge eating, emotional eating and unhealthy nutritional status such as overweight or obese.